Efeitos de antagonistas histaminérgicos H1 e H2 sobre a ansiedade e a memória emocional de camundongos - Kishi, Marcos Seizo (2009)
The aim of present work was to evaluate the effect of chlorpheniramine and zolantidine, histamine H1 and H2 antagonist respectively, on anxiety and on emotional memory in mice, through of two experiments. In the first experiment, forty-one male mice were divided into three groups, according to the pharmacological treatment consisting of intraperitoneal injections of 16 mg/kg of chlorpheniramine (CPA n=13), 20 mg/kg of zolantidine (ZOL n=14) or saline (SAL n=14). In the first day (T1), each mouse was tested for 5 minutes in an elevated plus-maze (EPM). The mice received the pharmacological treatment immediately after test, and 24 h later the animals were resubmitted to EPM (T2). Measures of learning and memory (open arm entries, open arm time, % open arm entries, and % open arm time) were analyzed. Two-way ANOVA showed significant differences within groups in % open arm entries and % open arm time. The student-Newmann-Keuls test for multiple comparisons revealed that both variables were reduced during Trial 2 for the animals treated with SAL, ZOL or CPA, thus indicating decreased open arm activity. In the conditions of the first experiment, chlorpheniramine and zolantidine were shown to have no effect on the consolidation of emotional memory in mice. In the second experiment we used 123 mice which were initially divided into 6 groups and which received i.p. injections of zolantidine (20 mg/kg) or chlorpheniramine at doses of 8.0 mg/kg or 16 mg/kg, each with its respective control (saline). Forty minutes after the injection the mice were for the first time exposed to EPM (T1). After 24 hours (T2), each group was subdivided into two new groups which were re-injected with one of the drugs or saline before re-exposure to the maze. In the two days it were evaluated behaviors related to anxiety (percentage of entries and length of stay in the open arms in T1), rates of learning and memory (reduction of percentage of entries and of length of stay in the open arms in T2), locomotor activity (entries in the closed arms). Zolantidine at a dose of 20 mg/kg, and chlorpheniramine at a dose of 8.0 mg/kg, showed no differences concerning the control, both in T1 and as in the comparison of data from T1 and T2. Furthermore, chlorpheniramine at a dose of 16 mg/kg, reduced activity in the open arms already in T1 and SAL-CPA and CPA-CPA showed no reduction of activity in the open arms in T2. The results suggest that zolantidine has no effect on anxiety or emotional memory, while chlorpheniramine presents an anxiogenic effect at a dose of 16 mg/kg.